The prediction of cutting force in end milling titanium alloy (Ti6Al4V) with polycrystalline diamond tools. (January 2017) - Pan, Wencheng; Ding, Songlin; Mo, John
Cutting force coefficients were conventionally described as the power function of instantaneous uncut chip thickness. However, it was found that the changes in the three controllable machining parameters (cutting speed, feed and axial cutting depth) could significantly affect the values of cutting coefficients. An improved cutting force model was developed in this article based on the experimental investigation of end milling titanium alloy (Ti6Al4V) with polycrystalline diamond tools. The relationships between machining parameters and cutting force are established based on the introduction of the new cutting coefficients. By integrating the effects of varying cutting parameters in the prediction model, cutting forces and the fluctuation of cutting force in each milling cycle were calculated. Validation experiments show that the predicted peak values of cutting forces highly match the experimental results; the accuracy of the model is up to 90% in predicting instantaneous cutting forces.